A novel hybrid polymer of PCL/fish gelatin nanofibrous scaffold improves proliferation and differentiation of Wharton's jelly‐derived mesenchymal cells into islet‐like cells. Issue 8 (20th April 2022) - Mirtaghi, Seyedeh Masoumeh; Hassannia, Hadi; Mahdavi, Mohammadreza; Hosseini‐khah, Zahra; Mellati, Amir; Enderami, Seyed Ehsan
Abstract: Background: Using a different source of stem cells to compensate for the lost beta cells is a promising way to cure diabetic patients. Besides, the best efficiency of insulin‐producing cells (IPCs) will appear when we culture them in an environment similar to inside the body. Hence, three‐dimensional (3D) culture ameliorates the differentiation of diverse kinds of stem cells into IPCs compared to those differentiated in two‐dimensional (2D) culture. In this study, we aim to create an ideal differentiation environment by using PCL/Fish gelatin nanofibrous scaffolds to differentiate Wharton's jelly‐derived mesenchymal cells (WJ‐MSCs) to IPCs and compare them with a 2D cultured group. Methods: The evaluation of cellular, molecular, and functional properties of differentiated cells on the 3D and 2D cultures was investigated by several assays such as electron microscopy, quantitative PCR, immunochemistry, western blotting, and ELISA. Results: The in vitro studies showed that WJ‐MSCs differentiated in the 3D culture have strong properties of IPCs such as islet‐like cells. The expression of pancreatic‐specific genes at both RNA and protein levels showed higher differentiation efficacy of 3D culture. Besides, the results of the ELISA tests demonstrate that in both groups the differentiated cells are functional and secreted C‐peptide and insulin in glucose stimulation, but the secretion of C‐peptide and insulin in the 3D culture group was higher than those cultured in 2D groups. Conclusion: Our findings showed the use of PCL/Fish gelatin nanofibrous scaffolds with optimized differentiation protocols can promote the differentiation of IPCs from WJ‐MSCs compared to the 2D culture group. Abstract : Islet‐like structures generated from wharton's jelly‐derived mesenchymal cells on PCL/Fish gelatin nanofibrous scaffold.